Взаємозв’язок остеоасоційованих гормонів і хімічних елементів у жінок з остеодефіцитом у пре- і постменопаузний періоди - Зябліцев, С. В.; Рибалко, Л. М.; Синяченко, О. В.; Тов, І. В. (Clinical Endocrinology and Endocrine Surgery, 2010)
The purpose of the given work is a comparative estimation of the concentration of osteoassociated hormones, macroelements (ОАМE) and microelements (ОАмE) in an organism, and also their interrelations in pathogenetic construction of osteodeficiency in menstruating women (1st group) and after menopause (2nd). The parameters ОАМE in blood of women of both groups correlate differently with the activity of alkaline phosphotaze, calcium regulating and sexual hormones, and levels of ОАмE are connected with the hormonal status indicators, but there is dimorphism in the 1st and 2nd groups concerning Li and Zn, that in a whole reflects additional features of pathogenesis of osteodeficiency (osteopenia and osteoporosis) at women in pre - and postmenopausal period.